2019
DOI: 10.1038/s42003-019-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human endothelin ETB receptor in complex with peptide inverse agonist IRL2500

Abstract: Endothelin receptors (ET A and ET B ) are G-protein-coupled receptors activated by endothelin-1 and are involved in blood pressure regulation. IRL2500 is a peptide-mimetic of the C-terminal tripeptide of endothelin-1, and has been characterized as a potent ET B -selective antagonist, which has preventive effects against brain edema. Here, we report the crystal structure of the human ET B receptor in complex with IRL2500… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…To measure the constitutive activity of GPCRs, we used the TGFα shedding assay, which measures accumulation of G q/11 and G 12/13 signaling, as described previously 62 , 63 . To detect G i -coupled GPCR, we utilized a chimeric Gα q/i1 subunit consisting of the Gα q backbone and the Gα i1 -derived 6 amino acids at the C-terminus, which is capable of binding to G i -coupled GPCRs and induces G q signaling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the constitutive activity of GPCRs, we used the TGFα shedding assay, which measures accumulation of G q/11 and G 12/13 signaling, as described previously 62 , 63 . To detect G i -coupled GPCR, we utilized a chimeric Gα q/i1 subunit consisting of the Gα q backbone and the Gα i1 -derived 6 amino acids at the C-terminus, which is capable of binding to G i -coupled GPCRs and induces G q signaling.…”
Section: Methodsmentioning
confidence: 99%
“…AP-TGFα release was calculated as described previously 63 and the signal in the mock-transfected conditions was set at the baseline. As a positive control for spontaneous Gi-coupled GPCR, we used a M4-DREADD (M4D), which loses affinity to the endogenous ligand acetylcholine, and introduced glutamine mutant at L123 3.43 , which is known to cause constitutive activity in other GPCRs 62 .…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the inverse agonist IRL2500 in the inactive ET B R structure [PDB ID: 6k1q ( 67 )] interacts, in addition to other residues, with an aromatic moiety directly at W336 6.48 in TM6, which is known generally for class A GPCRs to be a crucial trigger for receptor activation. This W 6.48 is located in the CWxP 6.50 motif involved in activation-related TM6 outward movement as part of the “global toggle-switch” activation model ( 81 , 82 ), also described as the “rotamer toggle switch” hypothesis ( 1 , 83 ).…”
Section: Lessons From Inactive State Structuresmentioning
confidence: 99%
“…BQ788 [ 85 ], A192621 [ 86 ], and IRL-2500 [ 87 ] are selective ET B receptor antagonists. Nagiri et al suggested that IRL-2500 acts as an inverse agonist by analyzing the structure of the IRL-2500/ET B receptor complex [ 88 ]. However, to date, only a few studies have attempted to examine the roles of ET B receptors in the treatment of diseases.…”
Section: Overview Of Endothelinmentioning
confidence: 99%